Control of typhoid fever: evaluating herd protection through public health use of typhoid VI polysaccharide vaccine - Ochiai, R (2011)
Typhoid fever remains an important public health problem globally. Cluster randomized effectiveness trials with typhoid Vi polysaccharide vaccine were conducted in Kolkata, India and Karachi, Pakistan, to provide evidence for vaccine introduction. While efficacy trials are limited to estimate vaccine's performance on the vaccine recipients, effectiveness trials consider the public health impact, notably the herd protection, or indirect effect, which can only be seen when vaccines are administered to groups rather than to individuals. The observed total protection by the Vi polysaccharide vaccine in school-aged children was consistent in Kolkata and Karachi (61% and 56%, respectively), and was associated with minimal side-effects. The total protection in young children, however, was different (80% in Kolkata and no protection in Karachi). The Kolkata trial demonstrated significant herd protective effects, as demonstrated by indirect protection of non-vaccinees (45%), which was not shown in the Karachi trial. The difference in the effectiveness estimates between the trials may be due to the difference in study design and the population characteristics. Immunogenicity studies were undertaken for randomly selected persons from both sites at pre-vaccination, 6 weeks, and 2 years post-vaccination. Serum Vi antibody titres (IgG) were measured through ELISA. At baseline, the GMTs were below the protective level for both sites. At six weeks after vaccination, though there is a significant increase in the GMTs in children from both site, the level of GMTs were significantly lower from those in Karachi (2,307.0 ELU vs. 1,189.1 ELU). GMT declined from 6 week to 2 year testing points for both sites but maintained the protective level. These effectiveness trials gave a conclusive evidence of the protection conferred by the Vi polysaccharide vaccine in children older than 5 years of age. Targeted vaccination programme in high endemic areas, as stipulated in the WHO Position Paper, suggest the potential for effective control of typhoid fever in places like India and Pakistan with the school-based Vi vaccination.